SOX2+ sustentacular cells are stem cells of the postnatal adrenal medulla - Alice Santambrogio; Yasmine Kemkem; Thea L. Willis; Ilona Berger; Maria Eleni Kastriti; Louis Faure; John P. Russell; Emily J. Lodge; Val Yianni; Bence Kövér; Rebecca J. Oakey; Barbara Altieri; et al. (Nature Communications)
Abstract Renewal of the catecholamine-secreting chromaffin cell population of the adrenal medulla is necessary for physiological homeostasis throughout life. Definitive evidence for the presence or absence of an adrenomedullary stem cell has been enigmatic. In this work, we demonstrate that a subset of sustentacular cells endowed with a support role, are in fact adrenomedullary stem cells. Through genetic tracing and comprehensive transcriptomic data of the mouse adrenal medulla, we show that cells expressing Sox2/SOX2 specialise as a unique postnatal population from embryonic Schwann Cell Precursors and are also present in the normal adult human adrenal medulla. Postnatal SOX2+ cells give rise to chromaffin cells of both the adrenaline and noradrenaline lineages in vivo and in vitro. We reveal that SOX2+ stem cells have a second, paracrine role in maintaining adrenal chromaffin cell homeostasis, where they promote proliferation through paracrine secretion of WNT6. This work identifies SOX2+ cells as a true stem cell for catecholamine-secreting chromaffin cells.